A Comparative Study of Advanced Oxidation Processes for Pentachlorophenol Degradation - Nurul Alvia Istiqomah (Jurnal Kimia Sains dan Aplikasi, 2025)
Pentachlorophenol (PCP) is a priority pollutant that is highly resistant to conventional water treatment methods. Advanced Oxidation Processes (AOPs) offer an efficient approach by combining oxidants with activators to produce radicals. Hydrogen peroxide () and peroxydisulfate () are oxidants with symmetrical peroxide bonds that effectively generate radicals through energy transfer. However, each produces distinct radicals, followed by different degradation mechanisms. A comprehensive comparison is crucial for adopting effective AOP technologies. This study evaluates the kinetic performance and cost-effectiveness of AOPs using  and , activated by ultrasound (US), UV light (UVC and VUV), and their combinations.  demonstrated superior performance, particularly under UV light, due to its pH stability and higher reactivity with PCP. The combination of US and VUV yielded the highest degradation rates, with  achieving the best overall performance ( = 0.75 ). Higher temperatures improved PCP degradation across all systems, with the US-VUV- system achieving the highest rate ( = 0.91 ) at 35°C. The VUV- system recorded the lowest activation energy ( = 4.77 ), indicating greater efficiency. -based systems, particularly VUV- and UVC-, emerged as the most efficient and cost-effective options, with the lowest energy consumption (4.65–4.80 ) and costs (Rp8,825–Rp9,064/). These results highlight  in UV configurations as the optimal choice for PCP degradation, offering effective treatment with reduced energy and chemical requirements.